2013
DOI: 10.2139/ssrn.2402076
|View full text |Cite
|
Sign up to set email alerts
|

Do Good Institutions Enhance the Effect of Technological Spillovers on Productivity? Comparative Evidence from Developed and Transition Economies

Abstract: This paper argues that institutional quality has both direct and indirect (moderating) effects on productivity of countries. These hypotheses are tested using a battery of institutional proxies (governance, economic freedom, intellectual property rights and ease of doing business) and two channels for technological spillovers (trade and FDI) in a panel of developed and transition economies. The results confirm that good institutions have positive and similar effects on productivity across the board. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 129 publications
0
15
0
Order By: Relevance
“…There may be huge disparities in features of institutions. According to Krammer (2015), "In practice, measuring institutions is a daunting task". In this regard, Mahendra et al (2015) stated that it is difficult to measure institutional variables as each country and region may have different understanding and perceptions on what institutions are.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be huge disparities in features of institutions. According to Krammer (2015), "In practice, measuring institutions is a daunting task". In this regard, Mahendra et al (2015) stated that it is difficult to measure institutional variables as each country and region may have different understanding and perceptions on what institutions are.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Poor institutions such as corruption may increase the R&D investment cost. Fifth, good governance such as strong intellectual property rights (IPRs) provide investors protections, thereby, facilitates investment in R&D (Krammer, 2015). In this regard, Ghosh and He (2015) stated that stronger investor protection reduces the manager's opportunistic behaviour to divert cash flow to them, therefore, more resources employed to value enhancing capital project like R&D. Moreover, Xiao (2013) stated that legal protection to shareholders reduces the agency conflict and solve the under and over investment problem of R&D activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchanan et al (2012) utilized an institutional perspective toward FDI and illustrated that good institutional quality is a critical determinant of FDI which along with correct macroeconomic environment, guarantees FDI stability. Also, considering FDI as a channel for spillovers of technological nature, Krammer (2015) confirmed that good institutions play a moderating role in the relationship between foreign technological spillovers and productivity.…”
Section: Fdimentioning
confidence: 74%
“…Earlier studies on technological catch-up by Gerschenkron (1962) compared a number of European countries to the then technologically more advanced Great Britain and stressed the importance of developing appropriate institutions. Empirical literature generally point to a positive relationship between institutional quality and T&K transfer in both developed and developing countries (Costantini & Liberati, 2014;Krammer, 2015).. Vasudeva (2009) showed that in the advanced economies of Japan, France, Norway and the U.S. socio-political institutions positively influenced knowledge-building strategies. Drine (2012) found that good institutions in developing countries in North Africa, Sub-Saharan Africa, and Asia and Latin America reduced the technology gap and quickened catch-up.…”
Section: Technology Institution Innovation Systems and Developmentmentioning
confidence: 99%